Comment accompagner les politiques de gestion urbaine et de décentralisation au Maghreb dans le contexte post-2011 ? Regards croisés d’acteurs de la coopération internationale et décentralisée - Jean-Philippe Bras; Aude Signoles (L’Année du Maghreb)
This article is a comparative perspective of interviews carried out with representatives of institutions conducting international cooperation and solidarity actions in the Maghreb. We interviewed our interlocutors on how their institutions have apprehended and analyzed the popular mobilisations of 2011, the political, legal and administrative changes induced by these mobilizations at the local level, the cooperation tools they have maintained or, specifically designed to support change, and on the type and profile of the actors with whom they now cooperate. The remarks given here are taken from our joint notes and not from a record of our interviews.